Precursor fractions of neurotensin and enkephalin might point to molecular mechanisms of cancer risk modulation during a lifestyle-intervention in germline BRCA1/2 gene mutation carriers - Grill, Sabine; Yahiaoui-Doktor, Maryam; Basrai, Maryam; Struck, Joachim; Schulte, Janin; Berling-Ernst, Anika; Engel, Christoph; Ullrich, Mirjam; Lammert, Jacqueline; Bischoff, Stephan C.; Schmidt, Thorsten; Niederberger, Uwe; et al. (Breast Cancer Research and Treatment, 2021)
Background: Germline BRCA1/2 mutation carriers (gBMC) face increased cancer risks that are modulated via non-genetic lifestyle factors whose underlying molecular mechanisms are unknown. The peptides Neurotensin (NT) and Enkephalin (ENK)—involved in tumorigenesis and obesity-related diseases—are of interest. We wanted to know whether these biomarkers differ between gBMC and women from the general population and what effect a 1-year lifestyle-intervention has in gBMC. Methods: The stable precursor fragments pro-NT and pro-ENK were measured at study entry (SE), after 3 and 12 months for 68 women from LIBRE-1 (a controlled lifestyle-intervention feasibility trial for gBMC involving structured endurance training and the Mediterranean Diet). The SE values were compared with a cohort of the general population including female subjects with and without previous cancer disease, non-suggestive for hereditary breast and ovarian cancer (OMA-reference). For LIBRE-1, we analysed the association between the intervention-related change in the two biomarkers and certain lifestyle factors. Results: At SE, gBMC had a higher median pro-NT than OMA-reference (in the subgroups with previous cancer 117 vs. 91 pmol/L, p = 0.002). Non-diseased gBMC had lower median pro-ENK levels when compared to the non-diseased reference group. VO2peak and pro-NT 1-year change in LIBRE-1 were inversely correlated (r = − 0.435; CI − 0.653 to − 0.151; p = 0.004). Pro-ENK correlated positively with VO2peak at SE (r = 0.323; CI 0.061–0.544; p = 0.017). Regression analyses showed an inverse association of 1-year changes for pro-NT and Omega-6/Omega-3 (Estimate: − 37.9, p = 0.097/0.080) in multivariate analysis. Conclusion: Our results give first indications for lifestyle-related modification particularly of pro-NT in gBMC.
CRIS-Team Scopus Importer:2023-03-08
Keywords: BRCA1/2 mutation carriers; Breast cancer; Cardiopulmonary fitness; Lifestyle intervention; Nutrition; Physical activity